EFFECTIVE ADMINISTRATIVE APPROACHES FOR MANAGING SAFETY AND SECURITY IN PUBLIC SECONDARY SCHOOLS IN ENUGU STATE (UNIZIK Journal of Educational Management and Policy, 2024)
The study adopted survey research design to examine administrative approaches for improving safety and security management in public secondary schools in Enugu state. Two research questions guided the study and the population of the study is 295 principals of public secondary schools in Enugu State. Simple random sampling technique was used to select 150 principals for the study.  The researcher developed instrument titled Administrative Approaches for Improving Safety and Security Management in Secondary School Questionnaire (AAISSMSSQ) was used for data collection. It contained 20 items designed in two clusters on a 4-point scale. The instrument was validated by three experts, two from the Department of Educational Management and Policy and one from Measurement and Evaluation in the Department of Educational Foundations, all in the Faculty of Education, Nnamdi Azikiwe University Awka. The instrument's reliability was determined using the Cronbach Alpha coefficient which yielded an alpha coefficient of 0.80. Mean and Standard Deviation were used to answer the research questions. The findings of the study showed that technology security systems approaches have not been deployed in the management of safety and security in public secondary schools in Enugu state while physical securities infrastructure have been deployed for improving safety and security management in secondary schools in Enugu State. Based on the findings, it was concluded that there is need to integrate both technology and physical securities infrastructure in the management of safety and security in secondary schools in Enugu State. The study recommended that government should be proactive in the review and implementation of technology security systems in schools and also Schools Administrators should make adequate provisions of the basic security systems in their schools to ensure an improved safety and security of both students and staff.
Keywords: Administrative, Approach, Safety, Security, Management, Secondary School